A Study of Whistleblowing Intentions in Government Sector - Indayani, Indayani; Yunisdanur, Vina (Universitas Muhammadiyah Malang)
This study aims to examine the effect of retaliation, status of wrongdoers, the level of wrongdoing seriousness, and organizational climate on whistleblowing intentions. The population in this study were Civil Servants (PNS) who work in the financial section of the Aceh Work Unit (SKPA) of 231 respondents. The data used in this study is primary data collected through a questionnaire survey. Statistical testing used in this study is multiple linear regression analysis with the help of the SPSS 20 application. The results of this study indicate that the retaliation and status of wrongdoers have a negative and significant effect on whistleblowing intentions, while the level of wrongdoing seriousness and organizational climate positively and significantly affect whistleblowing intentions. The contribution of this research is to provide an understanding to the entire State Civil Apparatus (ASN) to dare to report acts of fraud in the government environment, and to implement a whistleblowing system in order to reduce the level of fraud and corruption cases in Indonesia.